Calcific Myonecrosis of the Leg Treated by Debridement and Limited Access Dressing. (March 2013) - Sreenivas, T.; Nandish Kumar, K. C.; Menon, Jagdish; Nataraj, A. R.
Calcific myonecrosis is a rare late complication of limb trauma characterized by liquefaction and dystrophic calcification of muscles in the single compartment, usually in the leg. This occurs many years after the trauma and is probably due to chronic compartment syndrome. We report 2 cases of calcific myonecrosis involving the anterior compartment of the leg that presented to us in an advanced stage of multiple sinuses discharging calcific material. Incision and drainage had been attempted at a local hospital prior to presentation at our hospital resulting in a non healing wound. Both patients had a history of antecedent trauma to the leg a few years ago. Patients were treated by thorough debridement of the involved muscles in the anterior compartment. Limited access dressing (LAD) was used to manage the dead space left after debridement. After application of the LAD, the wound was covered with split skin grafting. In both patients, healing of the cavity following debridement was facilitated by application of limited access dressing. While the wound completely healed, the disability due to extensive debridement of anterior compartment of the leg persisted. At the latest follow-up, the patients were asymptomatic without any recurrence. Thorough debridement of the compartment involved and application of LAD may be another option of treating calcific myonecrosis of the leg, which was initially considered a "do not touch" lesion. Morbidity due to surgery and need of repeated surgeries for recurrences should be kept in mind and regular follow-up should be considered.